LINKING TEACHER PROFESSIONAL DEVELOPMENT NEEDS WITH APPROPRIATE SOLUTIONS: INSIGHTS FROM AN INIATIVE IN LATVIA - Greitāns, Kārlis; Eriņa, Dace; Namsone, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
International surveys have stated that each year teachers spend, on average, more than 10 days engaged in different professional development activities. The purpose for this investment in teacher professional development (TPD) is clear: teachers’ competence must develop according to changes in curriculum and 21st century requirements. In previous research we have developed a theoretical teacher competence framework, implemented it to identify teacher (N=263) groups competence gaps and professional development needs. The goal of this research is to link identified professional development needs related to the instruction of 21st century skills (criteria - instructional design, learning goals and feedback to students) with TPD solutions.This paper describes the development of a TPD model, based on evidence about teacher groups professional development needs, and its implementation in a school (N= 25 teachers). A TPD program, developed according to the model, combined face-to-face and online input workshops with collaboration in small groups to develop lesson plans. The topics of input workshops, (effective lesson design, lesson goals, effective feedback and reading comprehension) were chosen according to gaps, previously identified. To learn about appropriateness of the TPD model, the developed lesson plans, participant questionnaires and researcher field notes were analysed.